Legal Protection of Indonesian Citizens Who Are Victims of Human Trafficking in Myanmar - Azalia, Vania; Fahrazi, Mahfud; Hariyana, Trinas Dewi (Universitas Islam Indonesia, 2024)
This research examines the legal protections available to Indonesian citizens who are victims of human trafficking in Myanmar, focusing on the alignment of Indonesia's domestic laws with international standards. Specifically, it scrutinizes the harmonization of legal protection for witnesses and victims of human trafficking under Act Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons with the protocols established by United Nations Convention against Transnational Organized Crime, particularly its supplement, the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women, and Children. The study adopts a legal research methodology using a comparative law approach to analyze domestic and international legal frameworks. It investigates how well Act Number 21 of 2007 integrates the provisions of the UNTOC, noting areas of strong alignment and aspects that require further enhancement. The research finds that while Act Number 21 of 2007 is largely in sync with the UNTOC, it falls short in incorporating specific provisions for the special needs of trafficking victims, such as psychological support, housing, and rehabilitation services. The findings highlight significant steps taken by the Indonesian government to protect its citizens from human trafficking but also underscore the need for a more comprehensive approach that includes provisions for the unique needs of victims. The study advocates for amendments to the national legislation to fill these gaps and suggests a more robust framework for international cooperation to combat human trafficking in the region effectively.